Somatic Experiences as a Basis for Believing in Family Constellation Therapy - Medina, Arely (2025)
Family Constellation Therapy is a therapeutic approach that has gained great popularity in Mexico in recent years. This approach is set in the field of health and emotional well-being as well as in expressions of contemporary spirituality. Its practice allows the body and emotions to be key to perceive a symbolic and emotional effectiveness; in this way, it fosters in the subjectivity of practitioners a belief in it. The population studied in 2021 consisted of a group of women who regularly attend family constellation therapy sessions facilitated by a practitioner in Guadalajara. The aim of this study is to analize how, through the lived and somatized experiences of the participants, belief in the symbolic and emotional efficacy of the processes that occur during these therapies is legitimized. To understand this dynamic, we start with methodologies such as the incarnate field journal and somatic pedagogy, to attendthe affected in the field and to situate epistemologically somatic events, even those lived by the researcher in the field, and analyzed from a body anthropology, emotions and religion perspective, where therapeutic culture can be observed.